PENGARUH GAMBAR BERSERI TERHADAP KEMAMPUAN BAHASA EKSPRESIF ANAK USIA 5-6 TAHUN - Novialita, Jessica; Ali, Muhamad; Linarsih, Andini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the influence of storytelling methods using serial images on the expressive language skills of children aged 5-6 years in Kindergarten. The form of research used is parametric statistics and quantitative approach with one group pretest-posttest design. The source of this research data is children aged 5-6 years, totaling 16 children. The data collection techniques used in this study were observation, documentation, and tests using data collection tools for observation sheets, documentation and test sheets. The data were analyzed using the shapiro wilk normality test and the paired sample test table t test. The results showed that the average value of expressive language ability of children in class B2 before and after treatment was 7.31 to 11.62 this was evidenced from the results of the significance test of 0.000 0.05 and the results of hypothesis testing where t count t table was 14,429 2.1314 then Ha is accepted and Ho is rejected. So it can be concluded that there is a significant influence between the serial image media method and the expressive language skills of children aged 5-6 years in The Kindergarten.